Description of a new alpheid shrimp, Automate isabelae sp. nov. (Decapoda, Caridea, Alpheidae) found in fish stomach contents of the lane snapper Lutjanus synagris (Linnaeus, 1758), from the west coast of Florida, Gulf of Mexico - Ramos-Tafur, Gabriel E. (Zootaxa, 2018)
A new species of caridean shrimp of the family Alpheidae, Automate isabelae sp. nov., found in stomach analysis contents of the lane snapper Lutjanus synagris (Linnaeus, 1758), from the Keys and SW coast of Florida, Gulf of Mexico, is described. The abdomen and portions of the cephalic appendages were damaged in holotype, but remainder of the body and the chelipeds, whith the most important diagnostic characters are in decent or perfect condition, the description was further supplemented based on intact morphological parts of the paratypes. The presence of tubercles on the dorsal and ventral margins of the major chela palm, shows this new species to be related to the eastern Pacific Automate rugosa Coutière, 1902. Both congeners can be easily discriminated by the proportions and shape of the third maxilliped, the proportions and ornamentation of the carpus, merus, and chela of the major cheliped, the ventral seta of the carpus of the minor cheliped, the presence of a distoventral spine on the propodi of third and fourth pereopods, the armature of dorsal surface of telson, and their geographical distribution. The description of this new species increases the number of worldwide valid species known of the genus Automate to 12.